Efektivitas Problem Based Learning dalam Pembelajaran Akuntansi - Rafiqa Hastharita; Jasri Jasri (CV. ITTC INDONESIA, 2025)
This article aims to explore the effectiveness of Problem Based Learning (PBL) in accounting education through an in-depth theoretical review and literature analysis. PBL is widely recognized as a learner-centered approach intended to stimulate analytical, problem‐solving, and higher-order thinking skills which are essential competencies in accounting. This study employs a library research method by reviewing reputable journals from 2013 to 2024 that discuss PBL implementation in accounting courses, financial literacy education, auditing instruction, and the development of professional judgment. The analysis demonstrates that PBL improves conceptual understanding, strengthens technical reasoning, enhances student engagement, and increases accuracy in solving accounting cases. However, its effectiveness is influenced by several factors such as lecturer readiness, complexity of the problems presented, student digital literacy, and classroom management. This article concludes that PBL is an effective pedagogical model when implemented with proper scaffolding, structured assessment, and integration of real-world accounting cases.